The glyoxalase system of malaria parasites: implications for cell biology and general glyoxalase research - Urscher, Miriam; Alisch, Romy; Deponte, Marcel (Seminars in cell & developmental biology, 2011)
Malaria parasites of the genus Plasmodium have developed sophisticated mechanisms to benefit from the nutrient-rich environments of their hosts. For example, by hiding in red blood cells, they found a secure way to tap into the glucose supply of vertebrates. The high-power metabolism of Plasmodium leads not only to a significantly increased glucose consumption of infected erythrocytes, but also to an elevated production of d-lactate from methylglyoxal. The latter substance is a harmful by-product from glycolysis that is detoxified by the ubiquitous glyoxalase system. This system consists of reduced glutathione and two enzymes, the glyoxalases 1 and 2. Inhibition of the glyoxalases in the host/parasite unit is expected to be highly detrimental to the parasite. Moreover, by studying Plasmodium isozymes, physiological functions of the system beyond methylglyoxal conversion became prima facie obvious: (i) the two different active sites of glyoxalase 1 as well as the existence of (insular) glyoxalases in the apicoplast point to alternative substrates and metabolic pathways. (ii) The allostery of glyoxlase 1 and the monomer-dimer equilibrium of glyoxalase 2 suggest novel regulatory features of these enzymes. Here we review the current knowledge on the glyoxalase systems of the host/parasite unit, discuss their potential as drug target and summarize new hypotheses on glyoxalases with respect to general cell biology.
Gesehen am 01.12.2022